2002
DOI: 10.1055/s-2002-25359
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Complexes as Catalysts for the Intermolecular Hydroamination of Alkynes

Abstract: Several titanium complexes can be used as active catalysts for the intermolecular hydroamination of alkynes. The investigated catalysts include various titanocene complexes as well as titanium compounds bearing amido-and chloro-ligands. The activities of the investigated catalysts are compared in two representative hydroamination/reduction sequences.From a synthetic point of view hydroamination reactions of alkenes and alkynes are among the most desirable transformations in organic chemistry. However, efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008) Ind 2 TiMe 2 [6] (Ind = indenyl) as a highly efficient catalyst for the intermolecular hydroamination of alkynes, we found that Ind 2 TiMe 2 is also a suitable catalyst for the intramolecular hydroamination of alkenes. [7] However, a detailed comparison between the benchmark catalyst Ti(NMe 2 ) 4 and Ind 2 TiMe 2 regarding their scope and limitations has not been described yet.…”
Section: Introductionmentioning
confidence: 80%
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008) Ind 2 TiMe 2 [6] (Ind = indenyl) as a highly efficient catalyst for the intermolecular hydroamination of alkynes, we found that Ind 2 TiMe 2 is also a suitable catalyst for the intramolecular hydroamination of alkenes. [7] However, a detailed comparison between the benchmark catalyst Ti(NMe 2 ) 4 and Ind 2 TiMe 2 regarding their scope and limitations has not been described yet.…”
Section: Introductionmentioning
confidence: 80%
“…After full conversion, subsequent reduction using zinc-modified NaBH 3 CN in methanol at room temperature gave the secondary amine 3 a. [11] As a result of the highly selective Markovnikov functionalization, the branched isomer is produced with excellent regioselectivity (> 99 %) and yield.…”
Section: Resultsmentioning
confidence: 99%
“…Initiated by our early studies on Ti-catalyzed intermolecular hydroaminations of alkynes, many other Ti complexes have been identified as active hydoamination catalysts by our group 19 and the groups of Bergman, 20 Odom, 21 Beller, 22 Richeson, 23 Schafer, 24 and Ackermann. 25 However, a discussion of all the different Ti-catalysts identified so far is not the purpose of this article.…”
Section: Other Titanium Catalystsmentioning
confidence: 99%
“…19 While in the first reaction sequence (Scheme 23), a diarylalkyne (diphenylacetylene, 11) was reacted with an alkylamine (tert-butylamine, 19), a dialkylalkyne (3-hexyne, 24) and an arylamine (4-methylaniline, 32) were used for the second sequence (Scheme 24). A comparison of Schemes 23 and 24 indicates that titanocene-derived complexes are highly active catalysts for the reaction between diphenylacetylene (11) and tertbutylamine (19).…”
Section: Other Titanium Catalystsmentioning
confidence: 99%
See 1 more Smart Citation